The Use of CIPP in The Extensive Listening Course at PSDKU Program - Nikijuluw, Renata C G V (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2020)
This article includes similar readings on educational assessment. Specifically, it includes relevant reading papers on the essence of the assessment, its intent, and the various evaluation models and their advocates. It also provides similar readings on a separate assessment model, the CIPP (Context Input Process Product) model. Justifying the reasoning for the use of the CIPP model, this involves readings on the context, emphasis, strengths and shortcomings of the CIPP and its proponent. It also provides literature on the approaches used to gather soft data, such as questionnaires, interviews and the focus group debate